Case report: Visibly curative effect of dabrafenib and trametinib on advanced thyroid carcinoma in 2 patients - Peng, Xue; Lei, Jianyong; Li, Zhihui; Zhang, Kun (Frontiers in Oncology, 2023)
Background: Differentiated thyroid cancer accounts for the majority of thyroid cancers and has a good prognosis after standard treatment. However, there are still some complex and refractory thyroid cancers, including locally advanced differentiated thyroid carcinoma and medullary carcinoma (MTC), poorly differentiated thyroid carcinoma (PDTC), and anaplastic thyroid carcinoma (ATC). Here, we report the therapeutic response of 2 advanced thyroid carcinoma patients treated with dabrafenib and trametinib. Case presentation: Two elderly females presented to the clinic with neck masses, dyspnea, and dysphagia. Signs of the trachea and esophageal compression were markedly visible in computed tomography (CT) scan and ultrasonography. Pathologic diagnoses of PDTC were confirmed for both patients through ultrasound-guided fine-needle aspiration (US-FNA). Both patients were significantly relieved from dyspnea and dysphagia after a course of treatment with dabrafenib and trametinib, and their tumors gradually shrank during the follow-up period. Conclusion: Overall, this treatment modality is rare, but effective. By sharing these 2 case reports, we hope to provide a reference for the treatment of clinically similar patients with advanced thyroid carcinoma.